Hypertension in pregnant women - Gryglas, Piotr (Przewodnik Lekarza/Guide for GPs, 2007)
High blood pressure in pregnant women is an important cause of maternal, fetal, and neonatal morbidity and mortality. This review focuses on problems related to the diagnosis and treatment of hypertension in pregnancy as discussed in the recent guidelines for the management of arterial hypertension published by the European Society of Hypertension and the European Society of Cardiology.